2018
DOI: 10.1038/s41467-018-06957-w
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous X-ray diffraction studies of ion transport in K+ channels

Abstract: Potassium ion channels utilize a highly selective filter to rapidly transport K+ ions across cellular membranes. This selectivity filter is composed of four binding sites which display almost equal electron density in crystal structures with high potassium ion concentrations. This electron density can be interpreted to reflect a superposition of alternating potassium ion and water occupied states or as adjacent potassium ions. Here, we use single wavelength anomalous dispersion (SAD) X-ray diffraction data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…In general, following the original KcsA crystal structure, which indicated alternating water and K + ions within the sequential SF binding sites, these studies have assumed that conduction involves concerted movement of ions and water through the filter, requiring combined electrical and steric forces(Åqvist & Luzhkov, 2000),(Berneche & Roux, 2001). It has also been suggested that less coordinated transitions may be involved(Åqvist & Luzhkov, 2000; Furini & Domene, 2009), and more recent studies have suggested that, rather than alternating ions and water, K + ions can occupy adjacent sites in the SF and conductance is then governed by a direct knock-on mechanism(Kopec et al, 2018; Köpfer et al, 2014; Langan et al, 2018), such as we observe here for Kir2.2. Except for the starting configuration, K + ions unambiguously permeated the open Kir2.2 channel in a fully dehydrated state, via a direct knock-on mechanism, in which an ion entering the S4 site pushed the ion ahead to site S3 and then S2, leading to exit of the outermost ion on the extracellular side.…”
Section: Discussionsupporting
confidence: 68%
“…In general, following the original KcsA crystal structure, which indicated alternating water and K + ions within the sequential SF binding sites, these studies have assumed that conduction involves concerted movement of ions and water through the filter, requiring combined electrical and steric forces(Åqvist & Luzhkov, 2000),(Berneche & Roux, 2001). It has also been suggested that less coordinated transitions may be involved(Åqvist & Luzhkov, 2000; Furini & Domene, 2009), and more recent studies have suggested that, rather than alternating ions and water, K + ions can occupy adjacent sites in the SF and conductance is then governed by a direct knock-on mechanism(Kopec et al, 2018; Köpfer et al, 2014; Langan et al, 2018), such as we observe here for Kir2.2. Except for the starting configuration, K + ions unambiguously permeated the open Kir2.2 channel in a fully dehydrated state, via a direct knock-on mechanism, in which an ion entering the S4 site pushed the ion ahead to site S3 and then S2, leading to exit of the outermost ion on the extracellular side.…”
Section: Discussionsupporting
confidence: 68%
“…crystal structure, which indicated alternating water and K + ions within the sequential SF binding sites, most studies have assumed that conduction involves concerted movement of ions and water through the filter, requiring both electric repulsion between K + ions and diffusional movement of water molecules driven by osmotic pressure (Åqvist and Luzhkov, 2000;Bernèche and Roux, 2001). However, it has also been suggested that less coordinated transitions may be involved (Åqvist and Luzhkov, 2000;Furini and Domene, 2009), and more recent studies have suggested that, rather than alternating ions and water being obligatory, K + ions can occupy adjacent sites in the SF, with conductance then being via a direct ion-ion knock-on mechanism (Kopec et al, 2018;Köpfer et al, 2014;Langan et al, 2018). In our simulations, K + ions unambiguously permeated the open Kir2.2 channel via a direct knock-on mechanism, in which an ion entering the S4 site pushed the ion ahead to site S3 and then S2, leading to exit of the outermost ion on the extracellular side without accompanying water permeation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the construction of dedicated long-wavelength X-ray beamlines such as I23 at Diamond Light Source (Wagner et al, 2016), it finally became possible to collect X-ray data at wavelengths corresponding to the anomalous scattering edge of potassium. In an earlier study, we collected anomalous scattering data from NaK2K at the potassium adsorption edge which also showed that the selectivity filter is fully occupied with four potassium ions (Langan et al, 2018). This result is in agreement with several recent studies which re-examined crystallographic data (Kö pfer et al, 2014), MD simulations of ion flow through the selectivity filter (Kopec et al, 2018) and, most recently, hydrogen/deuterium exchange rates as monitored by NMR (Ö ster et al, 2019).…”
Section: Permeation Of Potassium Ionsmentioning
confidence: 99%